Rising After Disaster: An Analysis of Coping Mechanisms Among Tsunami Survivors 20 Years Later - Yahaya, Mahathir; Jamaluddin, Mohd Farizi; Adnan, Wardatul Hayat (Asian Social Work Journal, 2025)
The tsunami that struck Aceh on 26 December 2004 caused catastrophic destruction and an estimated loss of around 300,000 human lives. This natural disaster not only resulted in extensive physical devastation and total loss of property but also triggered significant psychological issues. Early research indicates that coping strategies play a vital role in strengthening resilience among disaster survivors and in preventing the onset of more severe psychological conditions. This study, therefore, examines the coping strategies used by tsunami survivors who lost family members during the disaster. A total of ten survivors who met the criteria of losing family members were selected using snowball sampling. This study employed a qualitative case study design. In-depth interviews were conducted individually until data saturation was reached. The data were then analysed thematically. Findings reveal that three (3) coping strategies were used by the informants: social support (for example, through cultural and community activities), religious coping involving prayer and other practices, and situational change, such as relocating, pursuing aspirations, and engaging in business. Collectively, these approaches enhanced the survivors’ mental and emotional resilience and strengthened their self-confidence, even twenty (20) years after the disaster.